Neisseria meningitidis carriage in Swedish teenagers associated with the serogroup W outbreak at the World Scout Jamboree, Japan 2015. Issue 4 (15th March 2018) - Jacobsson, Susanne; Stenmark, Bianca; Hedberg, Sara Thulin; Mölling, Paula; Fredlund, Hans
Abstract : The aims of the study were to estimate the carrier state of Neisseria meningitidis in Swedish teenagers and its association with an outbreak at the World Scout Jamboree in 2015 as well as to compare sensitivity of throat versus nasopharyngeal swab for optimal detection of carriage. In total, 1 705 samples (cultures n = 32, throat swabs n = 715, nasopharyngeal swabs n = 958) from 1 020 Jamboree participants were collected and sent to the National Reference Laboratory for Neisseria meningitidis for culture and molecular analysis. The overall positivity for N. meningitidis was 8% (83/1 020), whereas 2% (n = 22) belonged to a known sero/genogroup while the majority (n = 61) were non‐groupable. Throat sample is clearly the sampling method of choice, in 56 individuals where both throat and nasopharynx samples were taken, N. meningitidis was detected in both throat and nasopharynx in eight individuals, in 46 individuals N. meningitidis was only detected in the throat and in two individuals only in the nasopharynx. Carriage studies are important to provide knowledge of the current epidemiology and association between carrier isolates and disease‐causing isolates in a given population. Therefore, planning for a carriage study in Sweden is in progress.